The nexus between economic development and import demand in CARICOM economies - Birchwood, Anthony ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Examines the implications of economic development for income demand elasticity of imports with respect to the economies in CARICOM.